Correction: Using verb morphology to predict subject number in L1 and L2 sentence processing: A visual-world eye-tracking experiment. Issue 1 (31st May 2022) - Koch, Eva M.; Bulté, Bram; Housen, Alex; Godfroid, Aline
This article details a correction to: Koch, E. M., Bulté, B., Housen, A., & Godfroid, A. (2021 ). Using verb morphology to predict subject number in L1 and L2 sentence processing: A visual-world eye-tracking experiment. Journal of the European Second Language Association, 5 (1), 115–132. DOI:http://doi.org/10.22599/jesla.79 .